PENGARUH PENYULUHAN KESEHATAN DENGAN MEDIA AUDIO VISUAL TERHADAP SIKAP MEMILIH JAJANAN SEHAT PADA ANAK USIA SEKOLAH DI SDN GUNUNG SARI 02 UMBULSARI KABUPATEN JEMBER - Megawati; Zahruddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
School-age children are affected by a variety of snacks that are sold both at school and outside school. In the case of choosing snacks, children still pay less attention to safety and hygiene, due to lack of knowledge about snacks that are safe for consumption. Based on BPOM in Jember 2015, it was recorded that almost 90% of school children 's snacks contained dangerous substances such as borax (food thickeners), formalin (preservatives), and coloring agents. This study aims to determine the effect of counseling with audio visual media on the attitude of choosing healthy snacks for school-age children (9-10) years at SDN Gunungsari 02 Umbulsari, Jember Regency. The research design used was one group pre-test - post test with a quasy-experimental approach. The population in this study is school age children (9-10) years. A total of 28 school-age children (9-10) years were taken in total sampling. Data analysis using Chi Square Test. The results of this study indicate that students who have a favorable attitude (78.5%) and have an unfavorable attitude (21.5%). The results of the analysis obtained values ​​based on the Chi Square test obtained p value = 0.024 <α 0.05 means that there is an influence of health education with audio visual media on the attitude of choosing healthy snacks for school-age children (9-10) years at SDN Gunungsari 02 Umbulsari Jember Regency . Based on these results the school should provide health education to children by using health education